Tracing the production and fate of individual archaeal intact polar lipids using stable isotope probing - Kellermann, Matthias Y; Yoshinaga, Marcos Y; Wegener, Gunter; Krukenberg, Viola; Hinrichs, Kai-Uwe (ORGANIC GEOCHEMISTRY, 2016)
Analysis of cellular membrane lipids has been widely applied to describe the microbial community composition in natural systems. When combined with stable isotope probing (SIP) experiments, deuterium label (D2O) uptake into lipids enables assessment of microbial biomass production. We performed SIP on methane-rich, hydrothermally-heated sediments to examine the de novo production of individual archaeal intact polar lipids (IPLs) by mesophilic anaerobic methane oxidizing group-1 archaea (ANME-1). The greatest extent of label uptake was by phosphatidyl glycerol archaeol (PG-AR), reaching 50{%} of the medium's label concentration in only 10 days. This indicates PG-AR as an important cell membrane lipid during the active growth phase of mesophilic ANME-1. Much less label uptake was into intact polar glycerol dibiphytanyl glycerol tetraethers (GDGTs), especially for those bound to diglycosidic head groups. The low production of these GDGTs contrasts with their predominance in ANME-1-dominated natural samples. We attribute the differential label uptake among individual IPLs to the ANME-1 tetraether biosynthetic pathway. This mechanism likely involves head-to-head condensation of two molecules of PG-AR and progressive substitution of PG by glycosidic head groups. The observation that ANME-1 invest in the synthesis of diethers during optimum growth suggests intact ARs and/or phosphate-bearing tetraethers as important biomarkers for actively growing populations in natural environments, while the diglycosidic GDGTs appear to signal stationary ANME-1 communities. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: HOV Alvin (Human Occupied Vehicle)